Detection of ClfB, and its relationship with biofilm formation, methicillinresistance in staphylococcus aureus strains isolated from infected patients and healthy carriers from the city of Cartagena, Colombia - Quintero, Braizon
Stepanovic et al. and molecular detection of clfb gene was performed using endpoint PCR with specific primers. The main finding was that strains from carrier individuals were mainly weak- or non- biofilm producers, while strains isolated from infections were mainly strong and moderate biofilm-producers. Presence of clfb gene was not significantly associated with biofilm-forming ability nor methicillin-resistance. Our results may indicate that S. aureus strains causing skin and soft tissue infections tend to form strong biofilms. Although the main mechanisms implicated with biofilm formation are not completely known, it is possible that clfb gene could contribute to biofilm establishment. However, other molecular determinants may be implicated in the biofilm-forming process. Thus, more studies are needed to increase the knowledge on this process. to the IDEAM values. The area available on the roofs to install the PV system turned out to be at least 3463, 81 m2 throughout the year.